2022
DOI: 10.1002/solr.202200286
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐Film Oxynitride Photocatalysts for Solar Hydrogen Generation: Separating Surface and Bulk Effects Using Synchrotron X‐Ray and Neutron‐Based Techniques

Abstract: The conversion of solar light into hydrogen by photoelectrochemical water splitting is one of the potential strategies that can allow the development of a carbon‐neutral energy cycle. Oxynitride semiconductors are promising materials for this application, although important limitations must still to be addressed. One of the most important issues is physicochemical degradation of the semiconductor, at the interface with water, where the electrochemical reactions occur. In this regard, thin films, with well‐defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…56 Moreover, with respect to ex situ and more importantly in situ characterization, thin lm photoelectrodes are advantageous due to their well-dened and atomically at surfaces allowing the use of dedicated surface characterization technques. 74 For instance, ex situ and in situ neutron reectometry and grazing-incidence Xray absorption spectroscopy are used to explore surface modi-cations of oxynitride thin lms. 109,113 The study on SrTaO x N y showed, that the oxynitride surface undergoes a compositional change due to the dissolution of SrO x into the electrolyte enriching Ta and lattice Sr at the surface and the slight loss of nitrogen from the structure.…”
Section: Methods and Standards To Investigate Stability And Degradati...mentioning
confidence: 99%
See 3 more Smart Citations
“…56 Moreover, with respect to ex situ and more importantly in situ characterization, thin lm photoelectrodes are advantageous due to their well-dened and atomically at surfaces allowing the use of dedicated surface characterization technques. 74 For instance, ex situ and in situ neutron reectometry and grazing-incidence Xray absorption spectroscopy are used to explore surface modi-cations of oxynitride thin lms. 109,113 The study on SrTaO x N y showed, that the oxynitride surface undergoes a compositional change due to the dissolution of SrO x into the electrolyte enriching Ta and lattice Sr at the surface and the slight loss of nitrogen from the structure.…”
Section: Methods and Standards To Investigate Stability And Degradati...mentioning
confidence: 99%
“…Due to the roughness of particle based lms, the surface area being in contact with the electrolyte (solid-liquid interface) is signicantly enhanced resulting in higher photocurrents. 74,76 Although the syntheses of thin lm oxynitrides, using pulsed reactive crossed-beam laser ablation and radiofrequency magnetron sputtering, 76,127,128 are rather complex and the resulting photoelectrodes suffer from low photocurrents and limited scalability, epitaxially-grown lms can be very useful to investigate the activity of the exposed crystal facets on the performance for water splitting. For example, Burns et al found that (011) oriented LaTiO 2 N lms exhibited 30% higher photocurrents than those with (001) orientation, mostly due to a faster extraction of charges derived from photons in the visible region.…”
Section: Methods and Standards To Investigate Stability And Degradati...mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the challenging issues of oxynitride-based semiconductors is physicochemical degradation at the interface with water, where the electrochemical reaction takes place. To understand the degradation mechanism and to find strategies to mitigate such detrimental effects, Pergolesi et al [152] suggested that the study of solid-liquid interface can benefit enormously from the use of thin films with well-defined and atomically flat surfaces for synchrotronbased surface-sensitive X-Ray scattering methods and neutron reflectometry. Particularly, synchrotron radiation-based soft X-ray angle-resolved photoemission spectroscopy (SX-APRES) enables the probing of the k-resolved electronic structure in the subsurface region despite atmospheric surface contamination and provides the opportunity to explore materials, surfaces, and interfaces as well as their reactivity and evolution.…”
Section: Fabrication Of Batao 2 N Filmsmentioning
confidence: 99%